مسح للتطورات الاقتصادية والاجتماعيةفي منطقة الإسكوا 2007-2006 - United Nations Economic; Social Commission for Western Asia (United Nations, 2008)
The Survey lays out an overall annual picture of the Arab region’s state of economic and social development, as well as focusing on specific burning issues which pertain to economic and social developments in Arab countries.